Variations in Under-Five Mortality Estimates in Nigeria: Explanations and Implications for Program Monitoring and Evaluation. - Doctor, Henry (Maternal & Child Health Journal, 2013)
Millennium Development Goal (MDG) 5 aims at reducing under-five mortality by two-thirds between 1990 and 2015. However, monitoring this goal is a challenging task. With an estimated 162 million people in 2011, Nigeria is Africa's most populous country with generally poor maternal and child health indicators. Maternal mortality ratio was estimated at 545 deaths per 100,000 live births in 2008 and recent data show that under-five mortality rates have varied tremendously. This paper provides a synthesis of the data collection and estimation procedures used by the two major sources of child mortality data in Nigeria (the Multiple Indicator Cluster Surveys; and Demographic and Health Surveys) and the importance of reflecting on these dynamics in order to utilize the mortality estimates in program monitoring and evaluation. While efforts to seek explanations for the unstable trends in mortality rates are ongoing, this study calls for stakeholders to seek studies that employ more detailed and robust disaggregation methods that take into account the relative impact of socio-demographic, medical, and public health variables on mortality rates. This will be crucial in assessing the effectiveness of selected interventions in reducing mortality. Further, the study encourages collection, use, and triangulation of health and demographic surveillance system (HDSS) and other available data which could assist in monitoring progress towards achieving MDGs since HDSS as well as census or survey data would provide an opportunity to measure and evaluate interventions through longitudinal follow-up of populations.